Low-Cost High Performance Polyamide Thin Film Composite (Cellulose Triacetate/Graphene Oxide) Membranes for Forward Osmosis Desalination from Palm Fronds - Tarek S. Jamil; Rabab A. Nasr; Hussien A. Abbas; Tamer I. M. Ragab; Sinethemba Xabela; Richard Moutloali (Membranes, 2021)
Novel low-cost cellulose triacetate-based membranes extracted from palm fronds have been fabricated through the phase–inversion procedure. The cellulose tri-acetate (CTA) membrane was modified by incorporation of graphene oxide (GO) prepared from palm fronds according to the modified Hummer method as well as the preparation of polyamide thin film composite CTA membranes to improve forward osmosis performance for seawater desalination. The surface characteristics and morphology of the prepared CTA, GO, and the fabricated membranes were investigated. The modified TFC prepared membrane had superior mechanical characteristics as well as permeation of water. The performance of the prepared membranes was tested using synthetic 2 M Sodium chloride (NaCl) feed solution. The water flux (Jw) of the thin-film composite (TFC) (CTA/0.3% GO) was 35 L/m2h, which is much higher than those of pure CTA and CTA/0.3% GO. Meanwhile, the salt reverse flux TFC (CTA/0.3% GO) was 1.1 g/m2h), which is much lower than those of pure CTA and CTA/0.3%. GO (Specific salt flux of TFC (CTA/0.3% GO) substrate membrane was 0.03 g/L indicating good water permeation and low reverse salt flux of the TFC membrane compared to CTA. A real saline water sample collected from Hurgada, Egypt, with totally dissolved solids of 42,643 mg/L with NaCl as the draw solution (DS) at 25 °C and flow rate 1.55 L/min, was used to demonstrate the high performance of the prepared TFC membrane. The chemical analysis of desalted permeated water sample revealed the high performance of the prepared TFC membrane. Consequently, the prepared low-cost forward osmosis (FO) thin-film composite CTA membranes can be introduced in the desalination industry to overcome the high cost of reverse osmosis membrane usage in water desalination.